IDENTIFICATION OF FOOD FRAUD VULNERABILITY FACTORS FOR IN THE SPICE INDUSTRY - Pamungkasany, Prinia; Hunaefi, Dase (International Journal of Social Service and Research, 2024)
Food fraud is a serious problem in the spice industry. This research aims to identify the potential for food fraud in spice commodity supply chain using the Food Fraud Vulnerability Assessment Tool from the Safe Supply of Affordable Food Everywhere (SSAFE). The research was conducted through a case study on two spice commodity industries, namely PT A and PT B, located in Jakarta and Tangerang from June to December 2023. The results of the study indicated that the opportunity factor, the motivation factor, and the control action indicator have high vulnerability in both companies, while in the control action factor, there are indicators that have low vulnerability in PT Y. The preparation of mitigation strategies was obtained from the analysis of the relationship between vulnerability factors, opportunities, motivations and control measures which were then validated from literature sources. Based on the conclusion of the food fraud vulnerability analysis in this study, there were several suggestions that can be put forward to improve the strategy of handling food fraud.